Requiem for an assassin - Barry Eisler (New York Onyx, 2008)
Blackmailed by a rogue CIA operative to carry out three assassinations or see his best friend murdered, reluctant killer-for-hire John Rain struggles with moral dilemmas as well as his growing certainty that the operative is hiding a more sinister agenda.
Keywords: Rain, John (Fictitious character) -- Fiction. Japanese Americans -- Fiction. Murder for hire -- Fiction